2021
DOI: 10.4209/aaqr.210055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Air Quality Changes and Influencing Factors in Changchun during the COVID-19 Pandemic in 2020

Abstract: To study the air quality changes during the Corona Virus Disease 2019 (COVID-19) lockdown in Changchun, we analyzed the changes in pollution of six major pollutants (PM2.5, PM10, SO2, NO2, O3, CO) and correlated them with meteorological parameters, using meteorological data and pollutants concentration data. Regional transport pathways and potential source areas of pollutants were analyzed using the Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model and Potential Source Contribution Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Conversely, the change trends of the NO 2 and CO concentrations (major pollutants emitted from transportation) that demonstrate substantial correlations with roadway and air transportation were congruent with the transportation usage volume, except during the wet season (May to August). Similar findings were reported by Gao et al (2021) and Tian et al (2021) in China and Canada during the COVID-19 period, respectively, where NO 2 and CO were fairly correlated with the traffic volume, advocating for the importance of proper public transportation planning in addressing NO 2 and CO pollution. There was no statistical correlation observed between O 3 and traffic volume; however, high concentration up to 62 ppm observed in April may have been caused by reduced mobility ( Siciliano et al, 2020 ).…”
Section: Discussion Of Findingssupporting
confidence: 77%
“…Conversely, the change trends of the NO 2 and CO concentrations (major pollutants emitted from transportation) that demonstrate substantial correlations with roadway and air transportation were congruent with the transportation usage volume, except during the wet season (May to August). Similar findings were reported by Gao et al (2021) and Tian et al (2021) in China and Canada during the COVID-19 period, respectively, where NO 2 and CO were fairly correlated with the traffic volume, advocating for the importance of proper public transportation planning in addressing NO 2 and CO pollution. There was no statistical correlation observed between O 3 and traffic volume; however, high concentration up to 62 ppm observed in April may have been caused by reduced mobility ( Siciliano et al, 2020 ).…”
Section: Discussion Of Findingssupporting
confidence: 77%
“…Higher PM 2.5 concentrations were concentrated in three provincial capitals and surrounding cities, of which Jilin Province is sandwiched in the middle and has slightly better indicators than the other two provinces caused by the transmission from the highly polluted regions [ 42 ]. Previous studies concerning the perennial air mass trajectory movement pattern prove have shown that more than 60% of the polluted air masses come from Inner Mongolia in the north direction of Northeast China [ 43 ]. In contrast, Liaoning Province borders Bohai Bay and variable weather systems following the reduction of local emissions have resulted in the region being more affected by meteorological transport.…”
Section: Resultsmentioning
confidence: 99%
“…In all the five States studied, the concentration of O3 was higher in 2020 than the average from 2015 to 2019. This increase has also been observed worldwide and may be related to the chemical formation regime of O3 (Collivignarelli et al, 2020;Dutta and Jinsart, 2021;Gao et al, 2021;Grange et al, 2021;Lu et al, 2013;Sharma et al, 2020;Sicard et al, 2020), which in large cities is usually Volatile Organic Compounds (VOC) limited. According to Siciliano et al (2020), who evaluated the increase of O3 in Rio de Janeiro city, the greatest concentrations result from higher ratios of non-methane hydrocarbons (NMHC) and nitrogen oxides (NOx), i.e., more significant reduction of NOx than of NMHC.…”
Section: Changes Observed In Air Quality and Mobilitymentioning
confidence: 94%